Mapping the Milky Way with LAMOST– III. Complicated spatial structure in the outer disc. Issue 3 (20th June 2018) - Wang, Hai-Feng; Liu, Chao; Xu, Yan; Wan, Jun-Chen; Deng, Licai
ABSTRACT: We illustrate the complexity of the Galactic outer disc by fitting the stellar volume densities of red giant branch stars with a two-disc component model. The discs are confirmed to extend to R  ∼ 19 kpc. The radial density profile of the discs shows two breaks at R ∼ 11 and ∼14 kpc, respectively, which separate the radial profile into three segments with different scalelengths of 2.12 ± 0.26, 1.18 ± 0.08 and 2.72 kpc at R  < 11, 11 ≤ R ≤ 14 and R > 14 kpc, respectively. The first break is likely due to the sudden drop in the radial profile of the thin disc, which may be evidence of radial migration. Beyond 14 kpc, the thick disc becomes prominent and the transition from a thin to a thick disc leads to the second break. This implies that the geometrically defined thick disc is more radially extended than the thin disc. This is also supported by the larger scalelength of the thick disc in comparison with the thin disc. Meanwhile, the scaleheight of the thicker component increases from $0.637_{-0.036}^{+0.056}$ at R  = 8 to $1.284_{-0.079}^{+0.086}$  kpc at R = 19 kpc, showing an intensive flared disc. Moreover, rich substructures are displayed in the residuals of stellar density. Among them, the substructures D 14 + 2.0 and O 14 − 1.5 show a north–south asymmetry, which can essentially be explained by southward shifting of the thick disc. However, no significant overdensity is found for the Monoceros ring. Finally, the thick disc shows a ripple-like feature with unclear origin at 9 < R  < 10.5 kpc.